2011
DOI: 10.1007/s11133-011-9190-4
|View full text |Cite
|
Sign up to set email alerts
|

“Whoa! They Could’ve Arrested Me!”: Unsuccessful Identity Claims of Women During Police Response to Intimate Partner Violence

Abstract: Many jurisdictions in the U.S. have implemented mandatory arrest policies in an attempt to limit police officers' discretion in their arrest decisions when responding to intimate partner violence calls. Drawing from semi-structured interviews with female victims of intimate partner violence, I explore the ways in which mandatory arrest policies have influenced the identity work of women during their interactions with police officers. I focus specifically on women's "unsuccessful" identity claims: situations wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Mandatory charging policy places “the onus for laying charges on the police and Crown” (Brown, 2000: iii). Mandatory policies have generated controversies in regards to the identification of the perpetrator, taking into account victim needs, or simply removing latitude for police officers to handle an IPV situation (Leisenring, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Mandatory charging policy places “the onus for laying charges on the police and Crown” (Brown, 2000: iii). Mandatory policies have generated controversies in regards to the identification of the perpetrator, taking into account victim needs, or simply removing latitude for police officers to handle an IPV situation (Leisenring, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps not surprisingly, officers' perceptions of their work with IPV and IPV victims is in no way uniform (DeJong et al, 2008). Officers may not always agree on the appropriate actions that should be taken during response to IPV cases (Leisenring, 2011). A number of different factors-such as an officer's age, sex, and their experience level-may influence the likelihood of an officer making an arrest (Buzawa & Buzawa, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Police officers, judges, attorneys, and even victim advocates hold certain expectations of "good victims" and may expect women to present as nonaggressive, blameless, and/or cooperative (Dunn, 2001;Dunn & PowellWilliams, 2007;Leisenring, 2011). In her study of intimate stalking cases, Dunn (2001) found that some of the ways in which prosecutors and advocates characterized stalking victims included "compliant," "borderline," "histrionic," "combative," "saintly," "grounded," "accountable," "annoying," "demanding," "noncooperative," "credible," "innocent," "proactive," "a survivor," "a real victim," "'still' a victim," "too 'into' being a victim," and "not a typical victim" (p. 298).…”
Section: Theme 1: Not All Women Who Experience Ipv View Themselves Asmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a major gap in existing scholarship in terms of drawing on the narratives of Black women to understand their experiences of being charged for an IPV offense, and how they have been impacted following police intervention. Only a few studies have explored the context and experiences of women’s arrest from their perspectives ( Grace, 2019 ; Leisenring, 2011 ; Li et al, 2014 ; Rajah et al, 2006 ; West, 2007 ). Even fewer examine the experiences of Black women (i.e., Bundy, 2019 ; Dichter, 2013 ; Larance et al, 2019 ; Potter, 2008 ; Richie, 2012 ; West, 2007 ).…”
Section: Introductionmentioning
confidence: 99%